Report From the Professional Practice & Research Pillar - Downey, Chris (Operating Room Nurses Association of Canada Journal, 2020)
Greetings from the Chair of ORNAC’s Professional Practice & Research Pillar. This pillar oversees several committees for the ORNAC Executive and Board: Standards, Educational Programs, Research, and Awards.